Knowledge and practice on prevention of respiratory health problems among traffic polices of Kathmandu, Nepal - kandel, Kabita; Parajuli, Shobha; Tiwari, Sirjana (Journal of Chitwan Medical College, 2025)
Introduction: Air pollution is a significant public health issue in Kathmandu and Kathmandu is the most polluted metropolitan city in Southeast Asia. The study aimed to assess the level of knowledge and practice on the prevention of respiratory health problems among selected traffic polices in Kathmandu, Nepal. Method: A cross-sectional study was conducted in workplace setting, among traffic police of Kathmandu, Nepal. A non-probability purposive sampling technique was applied for the data collection using a self-administered questionnaire during 23 Apr to 04 May 2021. Ethical approval was taken from the Institutional Review Committee of Pokhara University. Those who refuse to participate and absent during data collection were excluded from the study. Informed consent was obtained from all respondents Data were entered in MS Excel and exported to SPSS version 25 for descriptive and inferential analysis using mean, frequency, percentage, and standard deviation. The chi-square test was used to find out the association between dependent and independent variables. Result: Out of 160 traffic police surveyed, 98(61.3%) had average knowledge on respiratory health problems. Similarly, 123(76.9%) had an average level of practice for the prevention of respiratory health problems. A statistically significant association was found between level of knowledge and level of education (p=0.000) and between the level of practice and level of education (p=0.02). Conclusion: The study found that the majority of the traffic police had an average level of knowledge and an average level of practice on the prevention of respiratory health problems.